THE SOUTH CHINA SEA: AN IMPACT TO INDONESIA MANGROVE AT THE HUMAN PERSPECTIVE ON ECOSYSTEM, FUNCTION, SERVICES AND BENEFIT - Sukardjo, Sukristijono (Malaysian Journal of Science, 2016)
With respect to the sustainability, utilization, conservation and protection, the mangrove ecology in Indonesia are described briefly along with their roles and function for the human being. Apart from their ecological value, the mangrove forests provide numerous commercial products, generating much needed economic opportunities in most of the islands in the country. These products represent a primary resource for coastal people and they have a direct impact on the forest ecology. Aspects of utilization both by traditional and modern methods presented as a consequent of human civilization. Keywords: Indonesia, Ecology, Mangroves, Function, Biodiversity, Utilization